Penggunaan Media Belajar Flash Card untuk Meningkatkan Komunikasi Anak Autis - Suyanti Suyanti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the use of flashcard learning media in improving the communication skills of autistic children. Autistic children often experience obstacles in communicating, both verbally and nonverbally, so interactive and visual learning methods are needed. Flashcards were chosen as the media because of their simple, interesting, and easy-to-use nature to convey information visually. This study uses a quantitative approach with an experimental research design. The subjects of the study were autistic children aged 4-6 years who attended Anggrek Mandiri Inclusive Kindergarten. It is hoped that this study will be able to improve the communication skills of autistic children, both in recognizing words and understanding certain concepts.